Promotion of microbial phosphate solubilization by clay minerals - Iglesias Barrera, Gustavo Andrés (2024)
A number of physical and chemical interactions between clays and microorganisms have been reported with strong influence on microbial physiology and ecology. However, clay influences on phosphate-solubilizing microorganisms (PSM) remains unknown. PSM are capable of converting low solubility phosphates into soluble orthophosphate that can be taken up by plants. PSM are commonly present in the soil, particularly in the rhizosphere where they maintain associative symbiosis with the host plant. This study aimed at investigating the influence of soil clays (kaolinite, gibbsite, goethite, and hematite) on phosphate solubilization by the fungus Aspergillus niger. In the first chapter, a literature review is presented addressing the potential use of PSM in agriculture. The interaction between clays and microorganisms is reported and the strategies to enhance microbial phosphate solubilization are described. In the second chapter, an investigation on the influence of kaolinite, gibbsite, goethite, and hematite, on organic acid production and phosphate solubilization by the fungal isolate A. niger FS1. The experiments were conducted in modified NBRIP medium containing 3 g L! of Araxá rock phosphate (RP) supplemented with clays at 250, 500, 1000, 1500, 2000, 2500, and 3000 g L'!. The media were inoculated with 10º fungal conidia and incubated for 7 days at 28ºC. AII clays promoted increases in Araxá RP solubilization. The addition of gibbsite and kaolinite to the culture media led to the highest values of soluble P recorded (453.68 and 407.61 mg L', respectively). Gibbsite increased oxalic acid production by the fungus 8.36 times that of the control treatment. Gibbsite and kaolinite also promoted higher yields of citric acid, with 15.69 and 8.93 mmol L' ', respectively. In the third chapter, the hypothetical mechanisms of promotion of phosphate solubilization by clays were verified. Clays were added directly to the culture media as described above or placed in plastic capsules to prevent direct contact of the particles with the fungus. The effects of increasing concentrations of Fe-EDTA, AlCls, and silicic acid on Araxá RP solubilization and organic acid production were also evaluated. The encapsulation of clay particles did not decrease RP solubilization, indicating that the direct contact of the clays with the fungal mycelium is not required to induce RP solubilization. Significant increases in soluble P (3.89 times that of the control treatment) and oxalic acid were observed with increasing concentrations of AlCl;. Fe-EDTA and silicic acid increased phosphate solubilization by only 29 and 11%, respectively, with no significant increases in oxalic and citric acid production. In the fourth chapter, we investigated the effect of kaolinite, gibbsite, goethite, and hematite on the solubilization of Araxá, Argélia, Bayovar, Catalão, Marrocos, and Patos de Minas RPs and aluminum, calcium, and iron phosphate. For this, modified NBRIP medium was supplemented with 3 g L! of each P source above. The media were inoculated with 10º fungal conidia and incubated for 7 days at 28ºC. Gibbsite was the most efficient clay at promoting the solubilization of all RPs tested, reaching 100% cof solubilization for the majority. Kaolinite was particularly effective at the solubilization of iron phosphate, reaching 80.9% of solubilization. Only goethite was capable of enhancing aluminum phosphate solubilization (22./2%). In the fifth chapter, a brief review is presented discussing the question: Are there really microorganisms specialized in phosphate solubilization or is this process merely a side-effect of other microbial metabolic activities? All the findings presented here offer new possibilities for developing innovative strategies to enhance RP solubilization using soil clays. Our results shed light on the interactions between soil clays and fungal hyphae that may operate in the soil to increase P availability to plants. They also improve our understanding on P dynamics in the soil involving PSM and clay minerals. Keywords: Soil clays, phosphate solubilization, organic acids, kaolinite, gibbsite, goethite, hematite, phosphate solubilizing microorganisms.